Secure performance analysis and pilot spoofing attack detection in cell-free massive MIMO systems with finite-resolution ADCs - Xianyu Zhang; Xiaoqiang Qiao; Tao Liang; Kang An (International Journal of Distributed Sensor Networks)
In this article, the secure communication in cell-free massive multiple-input multiple-output system with low-resolution analog-to-digital converters is investigated in the presence of an active eavesdropper. Specifically, in this article, the deterioration caused by the analog-to-digital converter imperfections on the accuracy of the channel estimation and secure transmission performance is studied. Besides, the additive quantization noise model is utilized to analyze the impacts of the low-resolution analog-to-digital converters. The minimum mean square error channel estimation results show that there is a nonzero floor caused by the coarse analog-to-digital converters. Then, the closed-form expressions for both the legitimate users achievable ergodic rate and the information leakage to the eavesdropper are derived, respectively. Moreover, tight approximated ergodic secrecy rate expression is also presented with respect to analog-to-digital converters quantization bits, number of antennas, pilot power, and so on. To degrade the impacts of the pilot spoofing attack, an active attack detection approach based on random matrix theory is proposed which can only be operated at one access point. Simulation results are provided to corroborate the obtained results and analyze the impacts of various parameters on system secrecy performance. Also, the superiority of the proposed active attacks detection method is confirmed via simulation results.